Logiques géographiques et sociales de l’enclosure des espaces résidentiels en France - François Madoré (Belgeo)
The progressive evolution of the meaning of residential enclosure in a country such as France is the central assumption of our research: it’s no more a representation of a strong property ownership but a strengthening movement of private appropriation of the residential (new condominiums or single housing master plan community) collective spaces. What methodology and data are likely to display this ? To understand this phenomenon, this paper will show a study based on the analysis of the representation of residential enclosure in the selling of new real estate programmes. Two ways will be explored. First of all, we have made an inventory of all the residential programmes in the first six-month period of 2002. In second time, we have made a semantic analysis of real estate selling brochures ; this last approach will be applied to discussions conducted with ten real estate developers who have intentionally integrated residential enclosure at different levels in their programmes.